Maternal Plasma Lipid Profile as a Potential Risk Factor for Spontaneous Preterm Labor (Razi Medical Journal, 2025)
This study seeks to assess whether the maternal plasma lipid profile acts as a risk factor for spontaneous preterm labor. In this hospital-based retrospective case-control research, 70 pregnant women were included in 35 cases of spontaneous preterm labor and 35 cases of term pregnancy who had labor pain and were admitted to the Maternity and Children Hospital (MCH) for delivery between January 2023 to January 2024. We used the logistic regression method to determine the plasma lipid profile for risk factors of spontaneous preterm labor. The case group had significantly higher plasma levels of low-density lipoprotein, triglycerides, and total cholesterol, 31.4%, 45.7%, and 17.1% than the control group, respectively. All the potentially risk factors with their p-value ≤0.05 were taken for logistic regression. linear regression the elevated levels of triglyceride, total cholesterol, and low-density lipoprotein was detected to be associated with 2.92-fold (1.62‑3.24,95% CI, p < 0.001), 3.31-fold (1.30‑4.99,95% CI, p = 0.001) and 2.88-fold (1.75‑3.19,95% CI, p = 0.002) higher risk of premature labor, respectively. A higher risk of spontaneous preterm labor may be associated with elevated serum levels of triglycerides, total cholesterol, and low-density lipoprotein, which could be regarded as a risk factor for this pregnancy issue.
Keywords: Spontaneous Preterm Labor, Term Pregnancy, Lipid Profile.